FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN MATA PADA PEKERJA WELDER DI PT. X KOTA BATAM TAHUN 2024 - Apceriana, Macxda; Sari, Chinta Yolanda; Irawati, Ice (Jurnal Liga Ilmu Serantau, 2025)
Eye complaints are an intensive stress on eye functions, such as the accommodation muscles in jobs that require detailed observation or the retina due to improper contrast. Symptoms of eye fatigue include blurred vision, red eyes, sore eyes, and reduced accommodation ability. During welding, the decline in eye function due to aging is also related to eye fatigue, as eye endurance decreases due to pressure or stress from occupational factors affecting the eyes.This study aims to determine the relationship between safe behavior, occupational health and safety (OHS) training, and skills with eye complaints among welders at PT. X in Batam City in 2024. This research is quantitative with a cross-sectional approach. The population consists of welders at PT. X in Batam City, with a sample of 60 workers. The research instrument used is a questionnaire as a measuring tool, analyzed using the chi-square statistical test. The study results show a significant relationship between safe behavior and eye complaints (p-value = 0.001), a relationship between OHS training and eye complaints (p-value = 0.002), and a relationship between OHS skills and eye complaints (p-value = 0.005). In conclusion, there is a significant relationship, as the p-value < α = 0.05. It is recommended that the company provide knowledge to ensure welders adopt safe behavior while working, pay attention to and offer OHS training, and require workers to obtain certification or expertise in welding to prevent eye complaints among welders.